Making Kenyan Urban Transportation System Smart: The Case of Eldoret Municipality - Cheboi, J. K.; Daudi, F.; Ngetich, J. K.; Kipkorir, K.; Sumukwo, J.; Njogu, J. (Africa Environmental Review Journal, 2022)
Transportation systems are the fundamental to the economic prosperity of any nation. Nonetheless, transportation itself more so the use of automobiles has unintended negative environmental impacts that threaten the very existence of humanity through production of green house gases leading to climate change. Other negative impacts of transportation include compromise with human safety through traffic accidents causing injury and even deaths. This study sought to establish urban mobility patterns within Eldoret Municipality as a means to establish a green transportation planning. Traffic modal split was measured at different Gordon points on the major routes traversing through Eldoret Municipality. Findings illustrates that transportation in Eldoret municipality is unsustainable. There is heavy use of automobiles as compared to greener options such as cycling and walking. The study concludes that in order to achieve green urban transportation system there is need for an integrated approach in the implementation of transportation policy. Provision of feasible and convenient alternatives to car use, provision of high-quality public transportation systems as well as secure and opportune walking and cycling facilities have been recommended as opportunities for making urban transport green in Eldoret Municipality